THU0627 Differences in DAS28-CRP and DAS28-ESR Influence Disease Activity Stratification in Rheumatoid Arthritis and Could Influence Use of Biologics, Treatment Efficacy Evaluations and Decisions Regarding Treat-To-Target: An Analysis Using The BSRBR-RA. (15th July 2016) - Hamann, P.D.H.; Hyrich, K.; McHugh, N.; Shaddick, G.; Pauling, J.
Abstract : Background: Disease activity in rheumatoid arthritis (RA) has traditionally been measured using the 28-joint count disease activity score (DAS28) using ESR. Use of DAS28 using C-reactive protein (CRP) in place of ESR is increasing. This study investigates the level of agreement between the DAS28-ESR and DAS28-CRP scores across different disease activity thresholds and identifies how patient characteristics may influence agreement. Objectives: To identify the interscore agreement between the DAS28-ESR and DAS28-CRP scores and identify if gender or body mass index (BMI) influence the level of agreement. Methods: Patients with concurrent measures of ESR and CRP were identified from the BSRBR-RA, enabling paired calculation of DAS28-ESR and DAS28-CRP. Paired scores were stratified by patients' baseline BMI and gender. Agreement between the scores was compared using Bland-Altman statistics and agreement matrices. Results: 5457 patients (mean age 56 yrs, 76% female) with 31, 084 data entries were identified where paired DAS28-ESR/DAS28-CRP scores could be calculated. Mean DAS28-ESR was 0.3 points (95% CI -0.8 - 1.4) greater than DAS28-CRP (4.4 (SD 1.7) and 4.1 (SD 1.6) respectively). Men had a lower mean difference between the two scores compared with women (DAS28-ESR > DAS28-CRP by 0.2 points (95% CI -1.0 – 1.3) vs. 0.4 points (95% CI -0.7 – 1.4) respectively). The results stratified by BMI were similar to the overall mean difference. Agreement between the two scores according to disease activity thresholds are shown in Table 1 . Conclusions: Overall, the DAS28-ESR classifies fewer patients in remission (15.6% vs. 19.5%) giving a score, on average 0.3 points greater than the DAS28-CRP, with women having a greater difference between the two scores than men. When categorising scores by disease activity thresholds, the DAS28-ESR/DAS28-CRP have lowest agreement at LDA. 54.4% of DAS28-ESR scores were classified as MDA when the paired DAS28-CRP was LDA, which could influence results in clinical trial reporting. Conversely, 20% of patients were classified as being in MDA by DAS28-CRP when the paired DAS28-ESR demonstrated HDA. This is of importance given NICE biologics guidelines, and shows that up to 20% of patients may not satisfy the criteria for biologic therapy if DAS28-CRP were used instead of DAS28-ESR. These results highlight the impact of using the DAS28-ESR or DAS28-CRP interchangeably, and the importance of using a consistent version of the DAS28. Disclosure of Interest: None declared